2018
DOI: 10.1093/jas/skx038
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of growth and fatness traits in two pig populations with different genetic backgrounds

Abstract: Improvement in growth and fatness traits are the main objectives in pig all breeding programs. Tenth rib backfat thickness (10RIBBFT) and days to 100 kg (D100), which are good predictors of carcass lean content and growth rate, respectively, are economically important traits and also main breeding target traits in pigs. To investigate the genetic mechanisms of 10RIBBFT and D100 of pigs, we sampled 1,137 and 888 pigs from 2 Yorkshire populations of American and British origin, respectively, and conducted genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…In theory, the backfat thickness traits of pig are a quantitative trait, and their genetic mechanism is complex and controlled by many genes with small effects. This quantitative genetics view is supported by most of the recent gene mapping researches, including genome-wide association studies [3,4,5]. Although these loci are associated with complex traits but are less effect and are not easily detected by genome-wide association analysis, they may be accurately mapped by sweep analysis because they have always been subjected to high-intensity artificial selection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In theory, the backfat thickness traits of pig are a quantitative trait, and their genetic mechanism is complex and controlled by many genes with small effects. This quantitative genetics view is supported by most of the recent gene mapping researches, including genome-wide association studies [3,4,5]. Although these loci are associated with complex traits but are less effect and are not easily detected by genome-wide association analysis, they may be accurately mapped by sweep analysis because they have always been subjected to high-intensity artificial selection.…”
Section: Discussionmentioning
confidence: 98%
“…Backfat thickness is an important breeding objective trait, because it indirectly affects carcass lean percentage, fat deposition, meat quality, and consumers’ acceptance of pork [2]. Although many genome wide association (GWA) studies have been conducted in the past decades with the development of molecular marker technology, the genetic mechanism affecting backfat thickness still appears to be confusing [2,3,4,5]. From the view of population genetics, the effect of artificial selection affecting backfat thickness would leave detectable selection signatures within the pig genome [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…According to GO and pathway analysis, we found that the adjacent genes of lincRNAs (<100 kb) were involved in glycosaminoglycan biosynthetic process, glycerophospholipid metabolism, and glycosaminoglycan catabolic process. Among them, glycerophospholipid metabolism is closely related to fat deposition (Ecker and Liebisch, 2014; Jiang et al, 2018). Thus, we speculate that lincRNAs may have a regulatory role in subcutaneous fat development.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of human living standards, the demand for lean meat rate of pigs is also increasing. The 10th rib BFT and days to 100 kg are the economically important traits in pigs and are commonly used to predict carcass lean meat content and growth rate in pig breeding programs, respectively (Guo et al, 2017; Jiang et al, 2018). Furthermore, a previous study indicated that a low amount of subcutaneous fat or backfat deposition means good growth performance (Zambonelli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymorphism studies of the PITX2 gene were carried out on humans and mainly focused on its associations with diseases [22][23][24]. In livestock, polymorphisms of the PITX2 gene have been reported to be related to the milk traits of dairy goats and the meat quality and growth of pigs [25][26][27]. However, the expression profile and polymorphisms of PITX2 remain unclear in poultry.…”
Section: Introductionmentioning
confidence: 99%